Outcomes of conception subsequent to methotrexate treatment for an unruptured ectopic pregnancy. Issue 2 (4th August 2017) - Svirsky, Ran; Ben‐Ami, Ido; Berkovitch, Matitiahu; Halperin, Reuvit; Rozovski, Uri
Abstract: Objective: To assess the risk of adverse pregnancy outcomes in subsequent pregnancies among women treated with methotrexate for ectopic pregnancy. Methods: In a retrospective single‐center study, data were assessed for women treated with methotrexate for ectopic pregnancy at Asaf Harofe Medical Center, Zerifin, Israel, between May 2004 and May 2014. Results: Overall, 226 women were treated with methotrexate for ectopic pregnancy and subsequently conceived. The median time from treatment to conception was 10 months (range 1–120 months), and 127 women conceived within 12 months of treatment. Except for early missed abortion—which affected 23 (10.2%) pregnancies—adverse pregnancy outcomes such as fetal malformations were rare. The frequency of early abortion was lowest for women who conceived within 6 months of treatment with methotrexate (3/93, 3.2%), increased between 6 and 23 months (15/83, 18.1%), and remained high thereafter (7/50, 14.0%; P =0.006). Conclusion: The frequency of fetal malformation in a subsequent pregnancy was low among women treated with methotrexate for ectopic pregnancy. The frequency of early missed abortion was lowest during the first 6 months after treatment with methotrexate. Abstract : The frequency of early missed abortion was lowest during the first 6 months after methotrexate was given for ectopic pregnancy.